Altered excitatory-inhibitory balance in the NMDA-hypofunction model of schizophrenia - Kehrer, Colin; Maziashvili, Nino; Dugladze, Tamar; Gloveli, Tengis (Frontiers in Molecular Neuroscience, 2008)
Schizophrenia is a common psychiatric disorder of high incidence, affecting approximately 1% of the world population. The essential neurotransmitter pathology of schizophrenia remains poorly defined, despite huge advances over the past half-century in identifying neurochemical and pathological abnormalities in the disease. The dopamine/serotonin hypothesis has originally provided much of the momentum for neurochemical research in schizophrenia. In recent years, the attention has, however, shifted to the glutamate system, the major excitatory neurotransmitter in the CNS and towards a concept of functional imbalance between excitatory and inhibitory transmission at the network level in various brain regions in schizophrenia. The evidence indicating a central role for the NMDAreceptor subtype in the etiology of schizophrenia has led to the NMDA-hypofunction model of this disease and the use of phencyclidines as a means to induce the NMDA-hypofunction state in animal models. The purpose of this review is to discuss recent findings highlighting the importance of the NMDA-hypofunction model of schizophrenia, both from a clinical perspective, as well as in opening a line of research, which enables electrophysiological studies at the cellular and network level in vitro. In particular, changes in excitation-inhibition (E/I) balance in the NMDA-hypofunction model of the disease and the resulting changes in network behaviours, particularly in gamma frequency oscillatory activity, will be discussed.